(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper focuses on the transition to the education for sustainable development (ESD) paradigm in Russian university education, defining the variety and scope of problems to be solved. A comparative study of the progress in various educational and research fields is presented. The prospects for further solutions are considered.